2018
DOI: 10.3390/ijerph15051046
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Intervention Practices for Smoking Cessation: A Large Survey in Hong Kong

Abstract: Previous studies have shown that nursing interventions are effective in helping people to stop smoking, but that the participation of nurses in tobacco control activities has been far from satisfactory. The primary objective of this study is to identify factors that encourage or discourage nurses from participating in providing smoking-cessation interventions to their clients, based on the 5 A’s (ask, advise, assess, assist, arrange) framework. A cross-sectional survey was conducted among 4413 nurses in Hong K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 27 publications
2
39
2
Order By: Relevance
“…Price et al (2006) reported that there was a significant but modest positive correlation between the use of the 5As model and older age of nurse-midwives in Ohio, USA. Mak et al (2018) reported that more mature nurses were more likely to participate in providing advice and assistance and in making arrangements in Hong Kong [51]. In addition, Sarna et al (2001) reported that younger age was associated with the greatest barriers to delivering tobacco interventions among nurse members of the Oncology Nursing Society in the USA [52].…”
Section: Discussionmentioning
confidence: 99%
“…Price et al (2006) reported that there was a significant but modest positive correlation between the use of the 5As model and older age of nurse-midwives in Ohio, USA. Mak et al (2018) reported that more mature nurses were more likely to participate in providing advice and assistance and in making arrangements in Hong Kong [51]. In addition, Sarna et al (2001) reported that younger age was associated with the greatest barriers to delivering tobacco interventions among nurse members of the Oncology Nursing Society in the USA [52].…”
Section: Discussionmentioning
confidence: 99%
“…However, a lack of training in reducing tobacco consumption and in cessation counseling is a primary barrier to the provision of SHS exposure reduction services by pediatric nurses [38]. A large scale survey conducted in Hong Kong ( n = 4413) revealed that the majority of nurses recognized that tobacco control is an importance health advocacy program, but only 40.6% of the nurses believed they are equipped with the knowledge and skills to help smokers to quit smoking and about 13.5–64.9% of the nurses would practice the recommended 5As (Ask, Advise, Assess, Assist and Arrange) to help smokers to quit smoking [39]. In Shanghai, only 25% of community general practitioners have ever undergone training in smoking cessation interventions [40].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the study point to the importance of systemic changes promoted by local public health nurses participating in smoking cessation programs. Nurses with training in smoking cessation interventions contribution to public health practice is recognized (Mak, Loke, & Wong, ). Nurses are the largest group of health providers and are well suited to provide interventions to helping smokers quit smoking (Sarna, Bialous, Chan, Hollen, & O'Connell, ).…”
Section: Discussionmentioning
confidence: 99%
“…This evaluation has additional limitations. First, in addition to traditional cigarette smoking, use of other tobacco products is preva- health practice is recognized (Mak, Loke, & Wong, 2018). Nurses are the largest group of health providers and are well suited to provide interventions to helping smokers quit smoking (Sarna, Bialous, Chan, Hollen, & O'Connell, 2013).…”
Section: Discussionmentioning
confidence: 99%